Interconnection of busbar‐free back contacted solar cells by laser welding. (29th May 2014) - Schulte‐Huxel, Henning; Blankemeyer, Susanne; Merkle, Agnes; Steckenreiter, Verena; Kajari‐Schröder, Sarah; Brendel, Rolf
Abstract We are presenting the module integration of busbar‐free back‐junction back‐contact (BJBC) solar cells. Our proof‐of‐concept module has a fill factor of 80.5% and a conversion efficiency on the designated area of 22.1% prior to lamination. A pulsed laser welds the Al metallization of the solar cells to an Al foil carried by a transparent substrate. The weld spots electrically contact each individual finger to the Al foil, which serves as interconnect between different cells. We produce a proof‐of‐concept module using busbar‐free cell strips of 25 × 125 mm2. These are obtained by laser‐dicing of a 125 × 125 mm2 BJBC solar cell. The fill factor of this module is increased by 3.5% absolute compared with the initial cell before laser‐dicing. This is achieved mainly by omitting the busbars and reduction of the finger length. The improvement of the module fill factor results in an increase in the module performance of 0.9% absolute before lamination in comparison with the efficiency of the initial 125 × 125 mm2 BJBC solar cell. Hence, this interconnection scheme enables the transfer of high cell efficiencies to the module. Copyright © 2014 John Wiley & Sons, Ltd.